2022
DOI: 10.1108/jet-03-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the same coin: accessibility practices and neurodivergent users' experience of extended reality

Abstract: PurposeThis paper explores the accessibility barriers faced by neurodivergent individuals regarding the use of Extended Reality (XR) technologies and the difficulties faced by developers in creating neurodivergent inclusive XR experiences.Design/methodology/approachThe authors carried out a survey with neurodivergent participants, and a series of semi-structured interviews with neurodivergent adults and XR developers.FindingsNeurodivergent individuals experience sensory overload when using XR technologies; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Lukava et al [36] 2022 Two sides of the same coin: accessibility practices and neurodivergent users' experience of extended reality…”
Section: Survey Studymentioning
confidence: 99%
“…Lukava et al [36] 2022 Two sides of the same coin: accessibility practices and neurodivergent users' experience of extended reality…”
Section: Survey Studymentioning
confidence: 99%
“…There has been research into recreating forms of sensory overload in VR to promote understanding (Pavanatto et al, 2020), explore neurodivergent users' experiences of MR and sensory overload (Lukava, Morgado Ramirez and Barbareschi, 2022) and the amount of senses in retail settings that lead to sensory overload (Doucé and Adams, 2020). However there is currently little research into investigating sensory overload and fading in VR so a balance can be found for two or more senses.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Similarly, those with mobility disabilities may face challenges in VR platforms requiring intricate physical movements or not supporting assistive devices. The use of extended reality (XR) technologies can result in sensory overload for neurodivergent individuals, and such individuals may face difficulties in accessing XR technologies due to the lack of integration of accessibility requirements in current software development practices [16]. Addressing challenges related to the Metaverse for educational purposes involves considering potential accessibility and integration difficulties for individuals with learning disabilities [6].…”
Section: Introductionmentioning
confidence: 99%